FROM READING TO ACTION: HOW DIGITAL TEXT TRANSFORMS INTO PRACTICAL SKILLS IN LEARNERS WITH F70 (American Journal of Technology and Applied Sciences, 2026)
The progressive digitisation of public services, healthcare, commerce, and civic participation across Central Asia has reconfigured the foundational conditions of social competence. For learners diagnosed with mild intellectual disability (F70 per the ICD‑10 classification of the World Health Organization), the capacity to navigate digital interfaces-to read on-screen instructions, interpret system notifications, and execute algorithmically structured sequences of practical actions-constitutes both a formidable cognitive challenge and a non-negotiable prerequisite for autonomous community participation. This article investigates the psycho-pedagogical mechanisms through which comprehension of instructive and informational digital texts is converted into reproducible, transferable practical skills within the curricular framework of Social-Domestic Orientation (SBO) instruction in the Republic of Uzbekistan. Drawing upon Vygotsky’s cultural-historical theory, Gal’perin’s theory of the stepwise formation of mental actions, Paivio’s dual-coding theory, and the Universal Design for Learning (UDL) framework developed by CAST, the study proposes a five-component didactic model-comprehension, algorithmic execution, self-regulation, digital safety, and skill transfer-and presents empirical evidence from a quasi-experimental intervention involving 64 learners across four educational institutions in the Tashkent region. Results demonstrate statistically significant gains in algorithmic accuracy (p < 0.01), a measurable reduction in characteristic error patterns, and improved generalisation of digital skills to previously unfamiliar interfaces. The findings contribute to the critically under-researched intersection of special education and digital literacy in post-Soviet Central Asian educational contexts.